PENINGKATAN KEAKTIFAN DAN HASIL BELAJAR SISWA PADA MUATAN IPS MELALUI PENERAPAN MODEL PROBLEM BASED LEARNING SISWA KELAS IV SDN TOTO MARGO MULYO - UMI NAFIATUL JANNAH; RISHE PURNAMA DEWI; JAROT PRAKOSO (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
The background of this research is the low activity and student learning outcomes due to the use of less varied methods, namely lectures and methods in the guidebook. The purpose of this study was to increase the activeness and learning outcomes of fourth grade students at SDN Toto Margo Mulyo using a problem based learning model. This research is a classroom action research. The subjects of this study were the fourth grade students of SDN Toto Margo Mulyo, totaling 31 students. Data collection techniques in this study used observation sheets, documentation and tests. Data analysis was used with quantitative descriptive analysis. The results showed that in the pre-cycle the average score obtained by students was 56.61 with 29% classical completeness. Student learning outcomes in the pre-cycle are included in the moderate criteria. Then in the first cycle there was an increase in the average score of 11.79 and classical completeness as much as 22.6% so that in the first cycle the average score obtained by students was 68.4 and classical completeness was 51.6%. Student learning outcomes in the first cycle are included in the high criteria. Furthermore, in the second cycle student learning outcomes have increased again. The average value increased by 15.5 and the increase in classical completeness was 32.3%. The average value in the second cycle is 83.9 and the classical completeness is 83.9%. Student learning outcomes in the second cycle are included in the high criteria. In the pre-cycle the average value of student activity is 45.32% and is included in the sufficient criteria. In the first cycle the average value increased by 17.15% so that the average value of student activity in the first cycle was 62.47% and was included in good criteria. Then in the second cycle the average value increased by 25.42% so that in the second cycle the average value of student activity was 87.69% and included in the very good criteria. It can be concluded that the problem based learning model can improve the learning outcomes and activity of fourth grade students at SDN Toto Margo Mulyo. ABSTRAKLatar belakang dari penelitian ini adalah rendahnya keaktifan dan hasil belajar siswa karena penggunaan metode yang kurang bervariasi yaitu ceramah dan metode yang ada pada buku panduan. Tujuan dari penelitian ini adalah untuk meningkatkan keaktifan dan hasil belajar siswa kelas IV SDN Toto Margo Mulyo menggunakan model pembelajaran problem based learning. Penelitian ini merupakan penelitian tindakan kelas. Subjek penelitian ini adalah siswa kelas IV SDN Toto Margo Mulyo yang berjumlah 31 siswa. Teknik pengumpulan data dalam penelitian ini menggunakan lembar observasi, dokumentasi dan tes. Analisis data digunakan dengan analisis deskriptif kuantitatif. Hasil penelitian menunjukkan pada pra siklus nilai rata-rata yang diperoleh siswa adalah 56,61 dengan ketuntasan klasikal 29%. Hasil belajar siswa pada pra siklus masuk dalam kriteria sedang. Kemudian pada siklus I terjadi peningkatan nilai rata-rata sebanyak 11,79 dan ketuntasan klasikal sebanyak 22,6% sehingga pada siklus I nilai rata-rata yang diperoleh siswa adalah 68,4 dan ketuntasan klasikal 51,6%. Hasil belajar siswa pada siklus I masuk dalam kriteria tinggi. Selanjutnya pada siklus II hasil belajar siswa mengalami peningkatan kembali. Nilai rata-rata mengalami peningkatan sebanyak 15,5 dan peningkatan ketuntasan klasikal sebanyak 32,3%. Nilai rata-rata pada siklus II adalah 83,9 dan ketuntasan klasikal 83,9%. Hasil belajar siswa pada siklus II masuk dalam kriteria tinggi.Pada pra siklus nilai rata-rata keaktifan siswa adalah 45,32% dan masuk dalam kriteria cukup. Pada siklus I nilai rata-rata mengalami peningkatan sebanyak 17,15% sehingga nilai rata-rata keaktifan siswa pada siklus I adalah 62,47% dan masuk dalam kriteria baik. Kemudian pada siklus II nilai rata-rata mengalami peningkatan sebanyak 25,42% sehingga pada siklus II nilai rata-rata keaktifan siswa adalah 87,69% dan masuk dalam kiteria sangat baik. Dapat disimpulkan bahwa model problem based learning dapat meningkatkan hasil belajar dan keaktifan siswa kelas IV SDN Toto Margo Mulyo.